Sugar and ethanol production process from sugarcane - Fernandes, Erika Squisato [UNESP]; Cristina Alves, Rosângela [UNESP]; Pagnocca, Fernando Carlos; Contiero, Jonas [UNESP]; Brienzo, Michel [UNESP] (My University, 2017)
Sugarcane has been grown for centuries in Brazil aiming to sugar production and, in the last decades, to ethanol production. The sugar production steps can be divided into two groups: preparation and juice boiling, and crystallization. The step of juice preparation includes receiving the raw materials, grinding for juice extraction, treating the juice, and evaporating it. During the crystallization, there is supersaturation, centrifugation, drying, and subsequent storage. The sugar manufacturing process results in the various types of sugars, such as raw crystal, brown, refined, liquid, among others. The crystal sugar is produced in crystalline form without refining. It is widely used in the food industry, for example, producing beverages and biscuits. The sugarcane juice is extracted by milling it or through a diffuser that is physical-chemically treated before the fermentation step. The fermentation or alcoholic fermentation converts juice sugars into cellular energy for the yeast, resulting in the production of ethanol and carbon dioxide. The fermented broth is distilled for the production of anhydrous or hydrous ethanol. Considering the importance of sugarcane for ethanol and sugars in the industries, this chapter presents an overview of ethanol and sugar production as well as the main sugar types and their application.